(untitled) (Research, Society and Development, 2020)
Objective: To describe the impact of social and family relationships on the construction of the personality of transsexual people. Methodology: Descriptive, qualitative research that used the Narrative method of life, carried out in the period from 2016 to 2019, with 19 transsexual participants and 14 family members. Data were collected through a narrative interview, a comprehensive analysis by Daniel Bertaux was carried out and Michel Foucault’s theoretical framework was adopted. Results: It was evident that the family and other social institutions reproduce and affirm normative dogmas and produce actions of discipline and control over the bodies of transsexual people during the maturation process in order to coerce the experience of gender identities. Strong intersubjective relationships appear as a possibility of reversing this rejection and acceptance of transsexuality. Conclusion: Social and family acceptance is a challenge for the acceptance and social inclusion of transsexual people by the family and other social segments.